Factors affecting the human error: representations of mental models for emergency management. (2017) - Petrillo, Antonella; Felice, Fabio De; Longo, Francesco; Bruzzone, Agostino
Human reliability is a crucial element in ensuring plant performance during an emergency condition. This is even more true as technology has been evolving exponentially in recent times. In fact, it is evident that technological developments imply a decrease of accidents owing to the use of redundancy and protection. But at the same time, the high technology complexity requires a sophisticated safety management systems and a high level of safety culture. The classical approaches are not sufficient to prevent the occurrence of extraordinary incidents and accidents in which the key element is represented by the 'human factor'. Thus, in this context, it is necessary to face the problem considering the human factor in an holistic way as the causation of several incidents and accidents. The analysis of human factors constitutes a highly interdisciplinary field of study not yet well defined. This paper deals with various aspects of human behaviour that can influence operator reliability. The aim of the research is to propose a novel methodological approach to simulate human errors in emergency condition. The new model is based on an integration of fuzzy cognitive maps techniques and analytic hierarchy process (AHP), a multi-criteria technique for organising and analysing complex decisions.